FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS TIDUR SELAMA PEMBELAJARAN JARAK JAUH (PJJ) PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA - Siska Rizki Annisa (2021)
The prevalence of sleep quality got worse during distance learning throughout the COVID-19 pandemic because students had to adapt to changes in the learning and academic process. This study aims to determine factors that influence sleep quality during distance learning in students of Faculty of Health Sciences UPN Veteran Jakarta through cross-sectional quantitative analytic. Sampling technique with proportionate stratified random sampling (n=355). The variables studied: internal factors (gender, stress, anxiety disorders) and external factors (smoking behavior, smartphone use, physical activity, and dietary habit). The research instruments used were PSQI, PSS-10, ZRAS, SAS-SV, IPAQ-sf, and AFHC. Bivariate analysis used chi-square test and multivariate analysis used multiple logistic regression test (α=0.05). The bivariate analysis indicates that stress, anxiety disorders, and smartphone use were associated with sleep quality (p<0.05). While the variables of gender, smoking behavior, physical activity, and dietary habits (p>0.05) showed no relationship with sleep quality. Based on the results of multivariate analysis, the variable that has the greatest influence on sleep quality is anxiety disorder. Students with anxiety disorders have a 5.55 times risk having poor sleep quality compared to students who do not experience anxiety disorders controlled by stress and smartphone use (95% CI 1.28 - 24.16). Students should prevent anxiety disorder by increasing their self-confidence and exercising regularly.